DNA methylation profiling identifies TBKBP1 as potent amplifier of cytotoxic activity in CMV-specific human CD8+ T cells - Yu, Zheng; Sasidharan-Nair, Varun; Buchta, Thalea; Bonifacius, Agnes; Khan, Fawad; Pietzsch, Beate; Ahmadi, Hosein; Beckstette, Michael; Niemz, Jana; Hilgendorf, Philipp; Mausberg, Philip; Keller, Andreas; et al. (PLoS Pathogens, 2024)
Epigenetic mechanisms stabilize gene expression patterns during CD8+ T cell differentiation. Although adoptive transfer of virus-specific T cells is clinically applied to reduce the risk of virus infection or reactivation in immunocompromised individuals, the DNA methylation pattern of virus-specific CD8+ T cells is largely unknown. Hence, we here performed whole-genome bisulfite sequencing of cytomegalovirus-specific human CD8+ T cells and found that they display a unique DNA methylation pattern consisting of 79 differentially methylated regions (DMRs) when compared to memory CD8+ T cells. Among the top demethylated DMRs in cytomegalovirus-specific CD8+ T cells was TBKBP1, coding for TBK-binding protein 1 that can interact with TANK-binding kinase 1 (TBK1) and mediate pro-inflammatory responses in innate immune cells downstream of intracellular virus sensing. Since TBKBP1 has not yet been reported in T cells, we aimed to unravel its role in virus-specific CD8+ T cells. TBKBP1 demethylation in terminal effector CD8+ T cells correlated with higher TBKBP1 expression at both mRNA and protein level, independent of alternative splicing of TBKBP1 transcripts. Notably, the distinct DNA methylation patterns in CD8+ T cell subsets was stable upon long-term in vitro culture. TBKBP1 overexpression resulted in enhanced TBK1 phosphorylation upon stimulation of CD8+ T cells and significantly improved their virus neutralization capacity. Collectively, our data demonstrate that TBKBP1 modulates virus-specific CD8+ T cell responses and could be exploited as therapeutic target to improve adoptive T cell therapies.
CRIS-Team Scopus Importer:2024-10-11

HLA reduction of human T cells facilitates generation of immunologically multicompatible cellular products - Winterhalter, Pascal M.; Warmuth, Linda; Hilgendorf, Philipp; Schütz, Julius M.; Dötsch, Sarah; Tonn, Torsten; Cicin-Sain, Luka; Busch, Dirk H.; Schober, Kilian (Blood Advances, 2024)
Adoptive cellular therapies have shown enormous potential but are complicated by personalization. Because of HLA mismatch, rejection of transferred T cells frequently occurs, compromising the T-cell graft’s functionality. This obstacle has led to the development of HLA knock-out (KO) T cells as universal donor cells. Whether such editing directly affects T-cell functionality remains poorly understood. In addition, HLA KO T cells are susceptible to missing self-recognition through natural killer (NK) cells and lack of canonical HLA class I expression may represent a safety hazard. Engineering of noncanonical HLA molecules could counteract NK-cell recognition, but further complicates the generation of cell products. Here, we show that HLA KO does not alter T-cell functionality in vitro and in vivo. Although HLA KO abrogates allogeneic T-cell responses, it elicits NK-cell recognition. To circumvent this problem, we demonstrate that selective editing of individual HLA class I molecules in primary human T cells is possible. Such HLA reduction not only inhibits T-cell alloreactivity and NK-cell recognition simultaneously, but also preserves the T-cell graft’s canonical HLA class I expression. In the presence of allogeneic T cells and NK cells, T cells with remaining expression of a single, matched HLA class I allele show improved functionality in vivo in comparison with conventional allogeneic T cells. Since reduction to only a few, most frequent HLA haplotypes would already be compatible with large shares of patient populations, this approach significantly extends the toolbox to generate broadly applicable cellular products.
CRIS-Team Scopus Importer:2024-07-19

Predicting T cell receptor functionality against mutant epitopes - Drost, Felix; Dorigatti, Emilio; Straub, Adrian; Hilgendorf, Philipp; Wagner, Karolin I.; Heyer, Kersten; López Montes, Marta; Bischl, Bernd; Busch, Dirk H.; Schober, Kilian; Schubert, Benjamin (Cell Genomics, 2024)
Cancer cells and pathogens can evade T cell receptors (TCRs) via mutations in immunogenic epitopes. TCR cross-reactivity (i.e., recognition of multiple epitopes with sequence similarities) can counteract such escape but may cause severe side effects in cell-based immunotherapies through targeting self-antigens. To predict the effect of epitope point mutations on T cell functionality, we here present the random forest-based model Predicting T Cell Epitope-Specific Activation against Mutant Versions (P-TEAM). P-TEAM was trained and tested on three datasets with TCR responses to single-amino-acid mutations of the model epitope SIINFEKL, the tumor neo-epitope VPSVWRSSL, and the human cytomegalovirus antigen NLVPMVATV, totaling 9,690 unique TCR-epitope interactions. P-TEAM was able to accurately classify T cell reactivities and quantitatively predict T cell functionalities for unobserved single-point mutations and unseen TCRs. Overall, P-TEAM provides an effective computational tool to study T cell responses against mutated epitopes.
CRIS-Team Scopus Importer:2024-09-13
Keywords: active learning; cross-reactivity; deep mutational scan; epitope; machine learning; mutation; T cell receptor; TCR-epitope prediction